THE INFLUENCE OF SHOPPING LIFESTYLE, FASHION INVOLVEMENT, AND PRODUCT QUALITY ON IMPULSE BUYING OF UMAMMA HIJAB PRODUCTS AMONG FEMALE STUDENTS OF THE MANAGEMENT DEPARTMENT, FACULTY OF ECONOMICS AND BUSINESS, MALIKUSSALEH UNIVERSITY. - Adnan, Adnan; Edyansyah, Edyansyah; Bahri, Syamsul; juliana, santi (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2024)
This study aims to investigate the influence of Shopping Lifestyle, Fashion Involvement, and Product Quality on Impulse Buying of Umama hijab products among female students in the Management Department of the Faculty of Economics and Business at Malikussaleh University. The sampling method used was non-probability sampling with incidental sampling, involving 105 respondents. Data analysis techniques included multiple linear regression analysis, classical assumption tests, instrument tests (validity and reliability), and hypothesis testing using SPSS 25.0. The results indicate that Shopping Lifestyle, Fashion Involvement, and Product Quality have a positive and significant effect on Impulse Buying both simultaneously and partially. Each variable”Shopping Lifestyle, Fashion Involvement, and Product Quality”positively and significantly influences Impulse Buying of Umama hijab products. The managerial implications suggest enhancing Shopping Lifestyle, Fashion Involvement, and Product Quality to boost Impulse Buying of Umama hijab products Keywords Shopping Lifestyle, Product Involvement, Product Quality, Impulse Buying.